Organizational Behavior and the Role of Marketing Strategies in Digital Business Competition - Murunga, James; Yazid, Mohamad Ezanee (PT Maju Malaqbi Makkarana, 2024)
In recent years, advancements in digital technology have significantly transformed business practices, creating an environment of tougher and more dynamic market competition. To navigate this competitive landscape, marketing strategy plays a critical role in enabling companies to achieve their goals. Effective marketing strategies in the digital era focus on reaching target markets more efficiently through digital tools and platforms, increasing competitive advantage through innovation and speed, enhancing brand visibility, and optimizing customer experiences. This study employs a literary reflection method (library research) to explore the intersection of marketing management and organizational behavior in the context of digital business competition. Organizational behavior, as a field of study, examines how individuals and groups function within organizations, contributing to the effective and efficient operation of businesses. Similarly, marketing management is the process of setting marketing objectives, analyzing marketing processes, and implementing strategies to achieve those objectives. This research highlights the importance of aligning organizational behavior with marketing management to ensure businesses can adapt and thrive in the digital age. By understanding these dynamics, companies can develop strategies that not only enhance operational efficiency but also foster a sustainable competitive edge in the marketplace.